Study of ectopic pregnancy in a tertiary care centre - Shukla, Dhirajkumar B.; Jagtap, Sunil V.; Kale, Pradnya P.; Thakkar, Hardik N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is a life threatening emergency leading to maternal death. Incidence of ectopic pregnancies has been increasing in last two to three decades with reduction in mortality. The presenting symptoms include abdominal pain, amenorrhoea and/or irregular vaginal bleeding. The present study was undertaken to study the clinical features of ectopic pregnancies in a tertiary care hospital. Methods: The present study on ectopic pregnancies was carried out in Department of Pathology, Krishna Institute of Medical Sciences, Karad, Maharashtra, India from January 2010 to June 2014. All the cases of ectopic pregnancy managed surgically were included in the study. Results: Total 102 cases of ectopic pregnancy were studied. Proportion of ectopic pregnancy in the present study is 1 in 205 deliveries. Majority of the cases (37) (36.27%) were noted between 21 to 25 years of age group followed by the age group 26 to 30 years. Ectopic pregnancy was most commonly noted in nulliparous women (44/102) (43.14%). Majority of the cases (50/102) (49.02%) had no risk factors. Abortion was the most common risk factor identified, alone as well as in conjunction with other factors. Ampulla was the most common site for ectopic pregnancy. 55% of the cases were on the right side where as 45% on the left side. We had 2 cases of heterotropic pregnancy with tubal ectopic in both the cases. The typical triad of amenorrhoea, pain in abdomen and bleeding was observed in 21.57% cases. Conclusions: The incidence of ectopic pregnancies is on rise as evident in this study. In order to reduce the morbidity and mortality due to ectopic pregnancies, there is need for early diagnosis especially in high risk cases.